2004
DOI: 10.1200/jco.2004.07.173
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variants in the UDP-glucuronosyltransferase 1A1 Gene Predict the Risk of Severe Neutropenia of Irinotecan

Abstract: UGT1A1 genotype and total bilirubin levels are strongly associated with severe neutropenia, and could be used to identify cancer patients predisposed to the severe toxicity of irinotecan. The hypothesis that the -3156G>A variant is a better predictor of UGT1A1 status than the previously reported TA indel requires further testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
655
4
14

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 918 publications
(702 citation statements)
references
References 25 publications
22
655
4
14
Order By: Relevance
“…Two variants of À3279T4G and the À3156G4A in the UGT1A1 enhancer region, and two nonsynonymous polymorphisms of 211G4A and 686C4A in exon1 were also associated with decreased enzyme activity for SN-38 glucuronidation. 5,6 The À3279 T4G in the UGT1A1 enhancer was very common (39.7%), while the À3156G4A variant was registered only 12.4% compared to 30% reported in a Japanese study. 11 The 211G4A (G71R) was found at a frequency of 14.8% over the combined groups, which is consistent with the frequency of 13-23% found in other Asian populations.…”
Section: Intra-ethnic Differences In Genetic Variantsmentioning
confidence: 74%
See 1 more Smart Citation
“…Two variants of À3279T4G and the À3156G4A in the UGT1A1 enhancer region, and two nonsynonymous polymorphisms of 211G4A and 686C4A in exon1 were also associated with decreased enzyme activity for SN-38 glucuronidation. 5,6 The À3279 T4G in the UGT1A1 enhancer was very common (39.7%), while the À3156G4A variant was registered only 12.4% compared to 30% reported in a Japanese study. 11 The 211G4A (G71R) was found at a frequency of 14.8% over the combined groups, which is consistent with the frequency of 13-23% found in other Asian populations.…”
Section: Intra-ethnic Differences In Genetic Variantsmentioning
confidence: 74%
“…Some genetic variants in UGT1A1 gene have been observed to have lower SN-38 glucuronidation rates and greater susceptibility to irinotecan induced gastrointestinal and bone marrow toxicity. [3][4][5][6] It is important that patients should be pre-screened and received reduced, safe irinotecan starting doses before treatment according to their genotypes. 7 Global studies of polymorphisms in UGT1A have shown alleles and genotypes to be unequally distributed among different ethnic human populations across the world.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The same common UGT1A1 variants associated with mild elevations of serum bilirubin are associated with diminished in vitro glucuronidation of the active irinotecan metabolite, SN-38, [19][20][21][22] and prolonged exposure and increased toxicity in patients receiving this agent. [23][24][25] As shown by Sai et al, 25 re-sequencing of the UGT1A1 gene in 85 Japanese patients treated with irinotecan confirmed that the haplotypes containing lower expression variants were associated with both a low SN-38G/SN-38 AUC ratio and elevated pretreatment bilirubin concentration. Importantly, however, additional haplotypes appeared to have distinct modifying effects on the SN-38 AUC ratio and total bilirubin level phenotypes, suggesting that more complete genetic variation data for UGT1A may better predict bilirubin and irinotecan metabolism phenotypes.…”
Section: Introductionmentioning
confidence: 84%
“…20,21 The clinical application of the genetic test for the UGT1A1*28 allele before irinotecan therapy has been in practice in the United States since 2005, based on a cumulative evidence supporting the significant association of this variant with severe irinotecan toxicity. 20,[22][23][24][25] The five most associated SNPs included rs4148323 (G4A, UGT1A1*6). Homozygotes of the UGT1A1*6 allele showed significantly high values in serum total bilirubin levels, supporting the evidence from earlier studies.…”
Section: Discussionmentioning
confidence: 99%